Performance of a Hybrid Wind-Grid-Load Energy System - Taleb, Maamar; Salman, Hussain A.; Jumaa, Hassan A.; Al-Mukharreq, Hassan A. (Journal of Technology Innovations in Renewable Energy, 2012)
A hybrid energy system consisting of a wind driven generator (WG) and a power utilities grid are interconnected. The hybrid energy system provides a constant power to an AC load regardless the surrounding weather conditions. The interconnection uses a controlled single phase full wave bridge rectifier. The bridge operates in the inverter mode of operation. This is done in purpose to guaranty the extraction of the real power from the wind driven generator. The extracted power is supplied to a constant AC load and any excess of power from the wind renewable energy source is injected into the power utility grid. At any pretended surrounding weather conditions, maximum extraction of power from the renewable energy source is targeted. This is done through the realization of a self-adjusted firing angle controller responsible of triggering the semiconductor elements of the controlled bridge rectifier. The performance of the proposed system has been simulated in MATLAB/SIMULINK environment and tested practically by building a laboratory prototype model. Quite satisfactory and encouraging results have been obtained.